PENDIDIKAN KESEHATAN TENTANG IMUNISASI PADA IBU DI POSYANDU DESA KEDUNGJAMBE SINGGAHAN - Nurus Safaah; Novia Dwi Astuti; Aris Puji Utami; Dwi Kurnia PS (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Immunization or immunity against disease threats is the main goal of vaccination. In essence, immunity can be possessed passively or actively. Both can be obtained naturally or artificially (Ranuh, 2008). Therefor it is necessary to do immunization to prevent disease attacks that affect the nutritional status of children. This activity was carried out on Wednesday, May 20 2020 at 09.00-10.00 at the Posyandu in the village of Kedungjambe Singgahan using the lecture and question and answer method using leaflet media. From the results of the Health Education carried out, it was found that the awareness of parents to give immunizations to their children was quite good, but there were some parents (mothers) who sometimes ignored the immunization schedule so that sometimes it was too late to give immunizations to children. Immunization is an effort to provide immunity to infants and children and pregnant women against certain diseases. Immunization of children under five at the Posyandu in Kedungjambe Singgahan village is generally quite good and most of them have met the immunization schedule, only a few mothers are sometimes late to give immunizations